The Relationship Between Tiktok Media Usage and Digital Literacy with Students’ Participation in Learning at SMKN 2 Karanganyar - Alif Zaim Sholahuddin Sholahuddin; Budi Tri Cahyono; Muhammad Aulia Alim (Universitas Sebelas Maret, 2026)
This study aimed to: (1) determine the relationship between TikTok usage and students’ participation in learning, (2) determine the relationship between digital literacy and students’ participation in learning, and (3) examine the simultaneous relationship between TikTok usage and digital literacy with students’ participation in learning at SMKN 2 Karanganyar. This research was motivated by the low level of student participation in classroom learning and the high intensity of TikTok usage among students, which potentially influences their learning engagement. The study employed a quantitative approach with an ex post facto correlational design. The population consisted of 432 tenth-grade students of SMKN 2 Karanganyar, with 191 students selected as the sample using cluster sampling techniques. Data were collected through questionnaires and documentation. The research instruments included questionnaires on TikTok usage, digital literacy, and student participation in learning based on the theories of participatory culture, UNESCO Digital Literacy Global Framework, and student engagement. Data analysis used multiple linear regression to examine partial and simultaneous relationships among variables. The results showed that: (1) there was a positive and significant relationship between TikTok usage and students’ participation in learning, (2) there was a positive and significant relationship between digital literacy and students’ participation in learning, and (3) there was a positive and significant simultaneous relationship between TikTok usage and digital literacy with students’ participation in learning. The findings indicate that educationally oriented TikTok usage supported by adequate digital literacy skills can enhance students’ behavioral, emotional, and cognitive engagement in the learning process. Therefore, schools and teachers are encouraged to utilize social media more pedagogically and strengthen students’ digital literacy to support optimal learning participation.